Proof of Concept Study for Fuselage Boundary Layer Ingesting Propulsion - Arne Seitz; Anaïs Luisa Habermann; Fabian Peter; Florian Troeltsch; Alejandro Castillo Pardo; Biagio Della Corte; Martijn van Sluis; Zdobyslaw Goraj; Mariusz Kowalski; Xin Zhao; Tomas Grönstedt; Julian Bijewitz; et al. (Aerospace, 2021)
Key results from the EU H2020 project CENTRELINE are presented. The research activities undertaken to demonstrate the proof of concept (technology readiness level—TRL 3) for the so-called propulsive fuselage concept (PFC) for fuselage wake-filling propulsion integration are discussed. The technology application case in the wide-body market segment is motivated. The developed performance bookkeeping scheme for fuselage boundary layer ingestion (BLI) propulsion integration is reviewed. The results of the 2D aerodynamic shape optimization for the bare PFC configuration are presented. Key findings from the high-fidelity aero-numerical simulation and aerodynamic validation testing, i.e., the overall aircraft wind tunnel and the BLI fan rig test campaigns, are discussed. The design results for the architectural concept, systems integration and electric machinery pre-design for the fuselage fan turbo-electric power train are summarized. The design and performance implications on the main power plants are analyzed. Conceptual design solutions for the mechanical and aero-structural integration of the BLI propulsive device are introduced. Key heuristics deduced for PFC conceptual aircraft design are presented. Assessments of fuel burn, NOx emissions, and noise are presented for the PFC aircraft and benchmarked against advanced conventional technology for an entry-into-service in 2035. The PFC design mission fuel benefit based on 2D optimized PFC aero-shaping is 4.7%.